Winter distribution and abundance of humpback whales (Megaptera novaeangliae) off Northeastern Brazil - Zerbini , Alexandre N.; Andriolo , Artur; da Rocha , Jesuina M.; Simoes-Lopes, Paulo Cesar; Siciliano , Salvatore; Pizzorno, Jose Luiz; Waite , Janice M.; DeMaster , Douglas P.; VanBlaricom , Glenn R. (J. Cetacean Res. Manage., 2023)
The Brazilian coast is recognised as a Southern Hemisphere humpback whale (Megaptera novaeangliae) wintering ground (IWC breeding stock ‘A’). The northeastern coast of Brazil was an important whaling ground in the 20th century. Shipboard sighting surveys were conducted in this area to evaluate large whales’ distribution and density in 1999 and 2000. Humpback whale sightings (n = 81, 153 individuals) were recorded using line transect methodology. Data from the 2000 survey were used to estimate abundance over the continental shelf from 5 to 12°S (20,040km2 ). A total of 872.1km were surveyed on effort. Humpback whales were distributed from nearshore to the 800m isobath, but 93.5% of sightings were recorded shoreward of the 300m isobath. The relatively high density off northeastern Brazil suggests that the species is reoccupying historical areas of distribution and the presence of newborn individuals indicates that calving and nursing occur in the area. The hazard rate model best fit perpendicular distance data. Abundance was estimated at 628 individuals (CV = 0.335, 95% CI = 327-1,157). This estimate probably corresponds to only a portion of the breeding population. Therefore, additional studies must be conducted to estimate the total size of the humpback whale population wintering off Brazil.